Large-thickness impact-wear-resistant nickel-based composite layer based on heterogeneous double wires and preparation method of large-thickness impact-wear-resistant nickel-based composite layer
By forming a nickel-based composite layer with alternate stacked reinforcement layers and toughened layer structures on the surface of the substrate, the local peeling and wear problems of the large-thick metal-based composite layer of laser powder cladding under extreme operating conditions is solved, and high toughness and impact wear resistance are improved.
Patent Information
- Application Number
- CN202411031409.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-30
- Publication Date
- 2025-03-11
AI Technical Summary
Under extreme operating conditions, the large-thick metal-based composite layer of laser powder cladding is prone to local peeling, particle fragmentation, fracture failure and other problems, resulting in material wear and waste of resources and economic losses.
A high-thick impact-resistant wear nickel-based composite layer preparation method based on heterogeneous double wire is adopted. The composite layer is formed on the surface of the substrate by laser cladding technology using alternate stacking reinforcement layers and toughened layer structures. The macroscopic and microscopic structure of the composite layer is controlled using different material components and melting transition modes of the toughened wire and reinforcement wire.
It effectively improves the toughness of the composite layer, reduces the driving force of crack propagation, significantly extends the service life of core components in extreme service environments, and improves the impact wear resistance of large-thick nickel-based composite layers.
Smart Images

Figure CN119592942A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of surface engineering technology, and in particular to a thick, impact-resistant and wear-resistant nickel-based composite layer based on heterogeneous double wires and a preparation method thereof. Background Art
[0002] In many manufacturing fields such as national defense, mining, metallurgy, energy and chemical industry, the problem of surface wear and failure of steel-based components is common. Ceramic particle reinforced metal-based composite layers have the advantages of high plasticity and toughness of metals and high hardness and high wear resistance of ceramics. They have not only been widely used in the field of wear resistance, but also promoted the rapid development of surface engineering and remanufacturing technology. Traditional coating technology has certain limitations in improving the surface properties of materials, especially when wear resistance, corrosion resistance, high temperature performance and other aspects need to be further improved. Advanced surface strengthening technology with laser as heat source has emerged and has become one of the important technologies in the field of advanced manufacturing in the 21st century. It has significant technical advantages and broad application prospects.
[0003] First of all, laser cladding technology is highly integrated and can realize the automation and intelligence of the cladding process, improving production efficiency and product quality. Secondly, laser cladding technology has the advantages of high precision and small heat-affected zone, and is suitable for surface strengthening of various materials, especially in the fields of high precision and high requirements. Cladding a composite layer on the surface of the substrate based on the principle of laser remanufacturing is one of the most promising ways to repair high-value parts. However, under extreme composite working conditions such as heavy loads and strong impacts, the use of laser powder to clad thick metal-based composite layers will cause local peeling, particle fragmentation, fracture failure and other problems, aggravating material wear, and causing huge waste of resources and economic losses. Therefore, there is an urgent need for a technology and method that can simultaneously ensure high wear resistance, high strength and excellent toughness on the surface of thick metal-based composite layers. Summary of the invention
[0004] In order to improve the problems of local peeling, particle fragmentation, fracture failure, etc. of laser powder cladding thick metal-based composite layers under extreme working conditions, the present application provides a thick impact-resistant and wear-resistant nickel-based composite layer based on heterogeneous twin wires and a preparation method thereof.
[0005] In a first aspect, the present application provides a method for preparing a thick, impact-resistant, and wear-resistant nickel-based composite layer based on heterogeneous double wires, using the following technical solution: A method for preparing a thick, impact-resistant, and wear-resistant nickel-based composite layer based on heterogeneous double wires comprises a laser cladding step, wherein the laser cladding step uses toughened wires and reinforced wires as cladding materials and adopts an alternating cladding method to form a composite layer of alternating toughened layers and reinforced layers on the surface of a substrate.
[0006] By adopting the above-mentioned strengthening layer and toughening layer to form an alternating stacking structure, the stress state at the crack tip in the thick ceramic particle reinforced metal matrix composite layer can be effectively alleviated, the driving force for crack propagation can be reduced, the toughness of the composite layer can be effectively improved, and the problems of local spalling, particle fragmentation, fracture failure, etc. of the composite layer can be improved.
[0007] Optionally, the composite layer is a two-dimensional layered alternating structure or a three-dimensional layered alternating structure.
[0008] Specifically, the two-dimensional layered alternating structure is a layered structure in which strengthening layers and toughening layers are alternately stacked in the thickness direction; the three-dimensional layered alternating structure is specifically: on a single layer plane, the strengthening layers and toughening layers are alternately stacked side by side along a first direction, and on adjacent single layer planes in the thickness direction, the strengthening layers and toughening layers are alternately stacked side by side along a second direction, and the first direction is perpendicular to the second direction, and this is repeated to form a three-dimensional layered alternating structure.
[0009] Optionally, both the toughened wire and the reinforced wire are powder core wires consisting of an outer layer and a filler; The outer layer of the toughened wire is a nickel matrix, and the filler includes NiBSi alloy powder and small-sized WC / W2C multiphase particles; The outer layer of the reinforcing wire is a nickel matrix, and the filler includes NiCrBSi alloy powder and large-sized WC / W2C multiphase particles; The particle size of the small-sized WC / W2C composite phase particles is 10-20 μm, and the particle size of the large-sized WC / W2C composite phase particles is 53-150 μm.
[0010] Under appropriate laser cladding conditions, the small-sized WC / W2C multiphase particles in the toughened wire can be completely dissolved in the molten pool, releasing W and C elements into the molten pool and inducing the precipitation of W2C particles; under appropriate laser cladding conditions, the large-sized WC / W2C multiphase particles in the strengthened wire are partially dissolved, and the particles diffuse elements at the solid-liquid interface, prompting the formation of an M6C phase "buffer layer" around the remaining large-sized particles, which is not only conducive to dispersing the stress in the matrix, but also acts as a strong skeletal structure to prevent local wear and failure of the metal matrix, thereby effectively improving the bearing capacity of the composite layer.
[0011] Optionally, the mass fraction of Cr element in the NiCrBSi alloy powder is 5%-10%.
[0012] The large-sized WC / W2C multiphase particles in the strengthening wire can partially dissolve in the nickel-based molten pool (control the strengthening wire in the insertion transition mode) and react with the Cr element in situ to form a quasi-continuous network distribution of W2C-M6C (η) phase composite carbide in the strengthening zone matrix. Therefore, by limiting the mass fraction of Cr in the NiCrBSi alloy powder, the amount of large-sized WC / W2C multiphase particles participating in the reaction can be further controlled.
[0013] Optionally, the toughened wire and the reinforced wire are respectively made of pure nickel tubes pre-filled with respective fillers through a drawing process, and the diameters of the toughened wire and the reinforced wire are respectively 1.2-2.4 mm.
[0014] The reinforced wire / toughened wire of the present application is made by filling WC / W2C multiphase particles and alloy powder into a pure nickel tube and then undergoing a drawing process. The wire is protected by a nickel matrix, which can prevent the WC / W2C multiphase particles from being excessively burned when exposed to a laser beam. Under laser cladding conditions, compared with the method of adding ceramic particles, the WC / W2C multiphase particles can be melted into one with the nickel matrix, and the interface bonding performance between the two is better. In addition, by using such a wire preparation method with pre-filled fillers, the proportion of the materials can also be controlled.
[0015] Optionally, the toughened wire and the reinforced wire are preheated using independent power supplies respectively, and under the control of the independent power supplies and laser energy, in the laser cladding step, the toughened wire is in a spreading transition mode and the reinforced wire is in an insertion transition mode.
[0016] The present application can control the laser energy and the resistive heat by controlling the laser output power and the preheating current of the independent power supply, and then under the coordinated control of the two independent heat sources, the strengthened wire can be controlled to melt in the insertion transition mode, while the toughened wire can be controlled to melt in the spreading transition mode.
[0017] The reason why the reinforced wire and the toughened wire adopt different melting transition modes is closely related to their own material composition design. Combined with the pre-structural design, the alternating deposition of the reinforced / toughened wires can be controlled, and finally the successful preparation of a thick impact-resistant and wear-resistant composite layer with a three-dimensional / two-dimensional layered alternating structure can be achieved.
[0018] Optionally, when laser cladding the toughened wire, the laser power is 1000 W, the preheating current is 70 A, the wire feeding speed is 1 mm / s, and the laser scanning speed is 3 mm / s; When laser cladding the strengthening wire, the laser power is 1300W, the preheating current is 60A, the wire feeding speed is 5mm / s, and the laser scanning speed is 3mm / s.
[0019] Since the tiny WC / W2C multiphase particles (10~20μm) filled in the toughened wire have a high solubility in the nickel-based molten pool, the photo-electric energy allocation can cause the added small-sized WC / W2C multiphase particles to be completely dissolved in the nickel-based molten pool under the liquid spreading transition mode; the large-sized WC / W2C multiphase particles are partially dissolved in the nickel-based molten pool under the insertion transition mode and react in situ with the Cr element to form a quasi-continuous network distribution of W2C-M6C(η) phase composite carbides in the strengthening zone matrix, and form a two-level reinforcement structure in the strengthening layer with the residual large-sized WC / W2C multiphase particles.
[0020] By limiting the laser power, preheating current and wire feeding speed as above, it is possible to achieve the purpose of melting the strengthening wire in the insertion transition mode and melting the toughening wire in the spreading transition mode.
[0021] Optionally, when laser cladding toughened wire, the temperature of the molten pool formed on the surface of the substrate is 1515K-1899K, and when laser cladding strengthened wire, the temperature of the molten pool formed on the surface of the substrate is above 1899K.
[0022] During laser cladding of toughened wire, the molten pool temperature is controlled to be greater than 1515K but lower than 1899K. According to the relationship between the Gibbs free energy of WC and W2C and the temperature, when the molten pool temperature is in this range, W2C is easy to precipitate in the molten pool, and the toughened layer of the composite is evenly distributed with native W2C (1~2μm) particles.
[0023] During laser cladding of strengthening wire, the molten pool temperature is controlled to be higher than 1899K, at which time the native W2C phase will precipitate preferentially; however, W2C is a metastable phase with low stability and easy dissolution in the nickel-based molten pool; when the molten pool temperature gradually decreases to the peritectic reaction interval of L+W2Cx→η, L+(W)+W2Cx→η, the W2C phase gradually dissolves and reacts in situ with the Cr-containing liquid phase to form a quasi-continuous network-distributed core-dendritic W2C-η phase composite carbide (10~15μm) in the strengthening zone matrix.
[0024] Optionally, the substrate includes any one of medium / high entropy alloys, carbon steel, stainless steel, nickel-based alloys, titanium alloys or aluminum alloys.
[0025] The preparation method of the composite layer provided in the present application has a wide range of applications, and is suitable for the above-mentioned metal materials with insufficient surface wear resistance, and is also very suitable for the remanufacturing of large-area and large-thickness parts.
[0026] In a second aspect, the present application provides a thick, impact-resistant, and wear-resistant nickel-based composite layer, which adopts the following technical solution: A thick nickel-based composite layer resistant to impact and wear, wherein the thickness of the composite layer is 3-100 mm.
[0027] The preparation method proposed in this application is suitable for the preparation of thick composite layers in the range of 3-100mm. The matrix in the strengthening layer is a nickel matrix, and the reinforcement structure is uniformly residual large-sized WC / W2C complex phase particles and native W2C-M6C complex phase carbides with quasi-continuous network distribution; the matrix in the toughening layer is a nickel matrix, and the reinforcement structure is native fine W2C particles; the strengthening layer and the toughening layer can be adjusted by the deposition strategy to achieve two-dimensional or three-dimensional alternating distribution, thereby forming a layered alternating or three-dimensional network interpenetrating reinforcement structure. Even for a thick composite layer, the two-dimensional / three-dimensional alternating stacking structure of the strengthening / toughening layer can effectively alleviate the stress state at the crack tip in the thick ceramic particle reinforced metal-based composite layer, reduce the driving force for crack propagation, and effectively improve the toughness of the composite layer. Therefore, this unique macroscopic strong / tough layer regular arrangement and the orderly combination of the microscopic reinforcement phase composition and spatial distribution within the layer can effectively improve the impact and wear resistance of the thick nickel-based composite layer, and significantly extend the service life of core components in extreme service environments.
[0028] In summary, the present application includes at least one of the following beneficial effects: 1. The two-dimensional / three-dimensional alternating stacking structure of strengthening layer / toughening layer designed in this application can effectively alleviate the stress state at the crack tip in the thick ceramic particle reinforced metal-based composite layer, reduce the driving force of crack propagation, and effectively improve the toughness of the composite layer. Therefore, this unique regular arrangement of macroscopic strong / tough layers and the orderly combination of microscopic reinforcement phase composition and spatial distribution within the layer can effectively improve the impact and wear resistance of thick nickel-based composite layers, significantly extend the service life of core components in extreme service environments, thereby realizing resource recycling and greatly promoting the sustainable development of the economy and society.
[0029] 2. In order to make the reinforcing particles present a spatially uniform distribution in the coating and obtain a strong ceramic-metal interface bonding, the present application does not simply adopt the traditional particle addition method or in-situ chemical reaction method to synthesize the reinforcing particles in the composite layer, but uses WC / W2C multiphase particles and other auxiliary alloying elements as precursors to induce the precipitation of the native reinforcement structure in the molten pool and together with the Ni-based wire as the original cladding material.
[0030] 3. The present application combines light (laser)-electricity (resistance heating) energy allocation to accurately control the molten pool temperature, thereby achieving controllable dissolution of the precipitation phase precursor WC / W2C in the original cladding material in the molten pool, releasing W and C elements in the molten pool, and then uniformly precipitating granular W2C particles (toughening layer) or M6C hard phase (strengthening layer) during the solidification of the molten pool, thereby achieving effective regulation of the multi-scale enhanced structure of the thick composite layer.
[0031] 4. This application adopts a laser cladding process based on heterogeneous twin wires, which not only has the characteristics of high deposition efficiency and high material utilization, but also can achieve diversity in deposition materials through wire composition design, providing the prerequisite for preparing large-thickness layered alternating nickel-based composite layers; in addition, two-dimensional layered alternating and three-dimensional layered alternating large-thickness nickel-based composite layers can be prepared by adjusting the twin-wire deposition strategy according to actual needs. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is a schematic diagram of the structure of a thick, impact-resistant, and wear-resistant nickel-based composite layer based on heterogeneous double wires of the present application, wherein Figure a shows a two-dimensional layered alternating structure, and Figure b shows a three-dimensional layered alternating structure; Figure 2 It is a schematic diagram of the preparation principle of the reinforced yarn and toughened yarn used in this application; Figure 3 It is a schematic diagram of the macroscopic and microscopic structure of the thick layered alternating composite layer obtained in the present application; Figure 4 A schematic diagram of the reasonable transition mode control of the strengthening yarn and the toughening yarn used in this application; Figure 5 is a metallographic morphology image of the two-dimensional layered alternating structure obtained in Example 1 of the present application; Figure 6 It is the wear performance result of the two-dimensional layered alternating structure obtained in Example 1 of the present application and the three-dimensional layered alternating structure obtained in Example 2 and the substrate Q345; Figure 7 This is the hardness test result of the two-dimensional layered alternating structure obtained in Example 1 of the present application. DETAILED DESCRIPTION
[0033] The inventor of this application has conducted in-depth research on the technical issues raised by the background technology of this application. The inventor believes that while introducing a ceramic phase into a metal matrix to improve the surface wear resistance, how to maintain its own toughness is the key to obtaining excellent impact and wear resistance. The inventor draws inspiration from the existing multi-material heterogeneous structures in nature (such as nacre and honeycomb), forms a multi-scale configuration design toughening concept, gives play to the multiple response mechanisms between different component structures and interfaces, and finally achieves composite toughening.
[0034] In response to different working conditions, the inventors have also studied a variety of metal-based composite materials including steel, titanium, nickel, aluminum and high entropy alloys. Since nickel-based alloys not only have good toughness and formability, but also have good wettability with high-hardness and high-wear-resistant tungsten carbide particles, this application focuses on the use of WC-Ni material system to prepare a wear-resistant composite layer on the surface of a steel substrate.
[0035] While the composite material system is constantly expanding, the inventors have also conducted corresponding research on the preparation process. The original materials used in the existing composite material preparation process using laser as the heat source are all powder materials, which not only makes it difficult to recycle the powder, but also has a low utilization rate. The added reinforcement phase in the mixed powder will be directly exposed to the high-energy laser beam during the processing. However, the general ceramic phase (such as carbide) has a higher energy absorption rate than metal powder, which not only easily causes excessive burning of particles, but also makes it difficult to regulate the characteristics of the original reinforcement phase, thereby affecting the performance of the composite material.
[0036] The wire-feeding laser cladding method has the advantages of high deposition efficiency, high material utilization, low processing cost and good operating environment, but the existing processes all use solid metal wires, which makes it difficult to prepare particle-reinforced composite layers. In terms of spatial structure toughening design, layered alternating composites are easy to optimize design and processing and can effectively overcome the inverted relationship between strength and toughness, and have attracted much attention. By adjusting the material deposition strategy, the cross-interlocking of the strengthening zone and the toughening zone in three-dimensional space can be achieved, greatly improving the damage tolerance. Layered composites are macroscopically divided into a strengthening layer (reinforced particle-enriched zone) and a toughening layer (generally a pure matrix). The characteristics of the precipitated phases in the strengthening / toughening layers are crucial to the wear resistance of the substrate serving under extreme working conditions.
[0037] In addition, the production of reinforced particles in the composite layer basically depends on the following two methods: one is called external addition, which refers to adding ceramic particles from the outside to the molten pool during the laser cladding process, and a composite layer can be formed as the molten pool solidifies; the other is called in-situ synthesis, which means that the elements forming the reinforced particles are built into the original cladding material. When a molten pool is formed on the surface of the substrate, a chemical reaction will occur, thereby forming reinforced particles, which are preserved during the cladding solidification process and finally form a composite layer. The advantages of the former external addition method are simple and easy to operate and easy to control the spatial distribution of particles. However, since the size of the external particles is generally larger, the gaps between the residual particles in the coating are too large; in addition, the interface bonding performance between the external particles and the substrate is weaker than that of the latter, which easily leads to insufficient wear resistance of the composite layer. The advantage of the latter in-situ synthesis method is that there is a strong metallurgical bond between the reinforced particles and the matrix, which greatly enhances the resistance to abrasive particles. Its disadvantage is that the traditional in-situ synthesis method requires the original cladding material to be prepared in advance according to the proportion of the theoretical chemical reaction. However, the laser cladding process is an extremely complex physical, chemical and thermal process, which includes the interaction between the high-energy laser and the cladding material and the resulting material melting, splashing of powder materials, non-equilibrium solidification of the molten pool and other phenomena. Therefore, the material concentration ratio in the molten pool has deviated from the theoretical value. Therefore, the composition and distribution of the reinforced particles in the composite layer after the final solidification are difficult to control, and thus the wear resistance of the composite layer cannot be guaranteed.
[0038] Therefore, if we want to further significantly improve the impact resistance and wear resistance of thick metal-based composite layers, we need to find a technical means to break through the existing bottleneck of laser cladding, so as to achieve a metal-based composite layer that combines high wear resistance, high strength and excellent toughness to face extreme working conditions, which is in line with the concepts and needs of advanced laser manufacturing.
[0039] Therefore, the inventor has obtained the following technical solution through innovative research.
[0040] In general, the inventors, starting from the metallurgical properties of the composite material system for laser melting (toughened wire Ni-WC / W2C, strengthened wire Ni-Cr-WC / W2C), proposed a heterogeneous double-wire laser melting technology and introduced an external synchronous preheating power supply, focusing on the three aspects of the preparation process, organizational structure characteristics and impact wear resistance of large-thickness heterogeneous layered alternating composite layers. Through the light (laser)-electric (resistance heat) energy allocation and combined with the wire composition design, the efficient and reliable preparation of large-thickness nickel-based composite layers with multi-scale structural enhancement can be successfully achieved. This method only needs to use appropriate process combination strategies to obtain the ideal coating structure, which is very suitable for the promotion and application of laser remanufacturing technology in the field of metal parts surface repair.
[0041] Specifically for the present application, the double-wire deposition strategy can be adjusted according to actual needs to prepare two-dimensional layered alternating and three-dimensional layered alternating thick nickel-based composite layers. Figure 1 This is a schematic diagram of the structure of a thick, impact-resistant, and wear-resistant nickel-based composite layer based on heterogeneous double wires of the present application, wherein Figure a shows a two-dimensional layered alternating structure, which is a layered structure in which strengthening layers and toughening layers are alternately stacked in the thickness direction; Figure b shows a three-dimensional layered alternating structure, which is specifically: on a single-layer plane, strengthening layers and toughening layers are alternately stacked side by side in a first direction, and on adjacent single-layer planes in the thickness direction, strengthening layers and toughening layers are alternately stacked side by side in a second direction, and the first direction is perpendicular to the second direction, and this is repeated to form a three-dimensional layered alternating structure.
[0042] The heterogeneous double-wire laser melting strategy adopted in this application relies on the precise control of the melting transition mode of two wires (reinforced wire and toughened wire). Combining the laser energy with the wire resistance preheating, the reinforced wire can be controlled to melt in the insertion transition mode, while the toughened wire can melt in the spreading transition mode. The reason why the reinforced / toughened wires adopt different melting transition modes is closely related to their own material composition design. Combined with the pre-structural design, the alternating melting of the reinforced / toughened wires can be controlled, and finally the successful preparation of a thick impact-resistant and wear-resistant composite layer with a three-dimensional / two-dimensional layered alternating structure can be achieved.
[0043] To achieve this goal, this application relies on the design and preparation of powder core wires, laser melting strategies and spatial structure design: First of all, the design and preparation of powder core wire is a prerequisite for the controllable construction of multi-scale reinforced structures of layered alternating nickel-based coatings. Figure 2 This is a schematic diagram of the preparation principle of the reinforced yarn and toughened yarn used in this application. Figure 2 As shown in the figure, the toughened wire (A#) is prepared by using the NiBSi-WC / W2C (10~20μm) material system and the drawing process. Specifically, the outer skin of the toughened wire (A#) is composed of pure nickel, and the inner filling is a powder containing NiBSi auxiliary metallurgical elements and small-sized WC / W2C multiphase particles. The NiBSi structure has low hardness and good toughness. The small-sized WC / W2C multiphase particles in the toughened wire can be completely dissolved in the nickel-based molten pool (controlling the wire in the spreading transition mode), inducing the uniform precipitation of W2C phase in the toughened layer. The spherical tungsten carbide particles are eutectic particles of multiphase WC / W2C (including WC and W2C), and their particle size is 10~20 microns. The purpose of selecting a small particle size range (10~20 microns) is that the smaller sintered particles have a higher solubility in the molten pool, which is easy to achieve complete dissolution in the molten pool, and then release W and C elements in the molten pool, creating the primary chemical environment for the precipitation of W2C particles.
[0044] The reinforcing wire (B#) is prepared by WC / W2C (53~150μm)-NiCrBSi system material system and drawing process. Specifically, the outer skin of the reinforcing wire (B#) is composed of pure nickel, and its internal filling is a powder containing NiCrBSi auxiliary metallurgical elements and large-sized WC / W2C complex phase particles. NiCrBSi alloys have good hardness and wear resistance at both room temperature and high temperature. The tungsten carbide spherical particles are eutectic particles of complex phase WC / W2C (including WC and W2C), with a particle size of 50~153 microns, and its manufacturing process is agglomeration sintering method. The large-sized WC / W2C multiphase particles in the strengthening wire are partially dissolved in the nickel-based molten pool (the strengthening wire is controlled to be in the insertion transition mode) and react in situ with the Cr (5~10wt.%) element to form a quasi-continuous network-distributed W2C-M6C(η) phase composite carbide in the strengthening zone matrix, and form a two-level reinforcement structure in the strengthening layer with the residual large-sized WC / W2C multiphase particles, which can effectively protect the metal matrix from micro-cutting by virtue of the macro / micro "shadow effect". Combined with the uniformly distributed native W2C in the toughening layer, it can not only effectively prevent the cracking problem of the thick deposited layer, but also significantly improve the impact wear resistance of the composite layer.
[0045] Figure 3 This is a schematic diagram of the macroscopic and microscopic structure of the thick layered alternating composite layer obtained in this application. Figure 3The matrix in the strengthening layer is a nickel matrix, and the reinforcement structure is uniform large-sized residual WC / W2C multiphase particles and native W2C-M6C multiphase carbides with a quasi-continuous network distribution; the matrix in the toughening layer is a nickel matrix, and the reinforcement structure is native fine W2C particles; the strengthening layer and the toughening layer can be adjusted through the deposition strategy to achieve two-dimensional or three-dimensional alternating distribution, thereby forming a layered alternating or three-dimensional network interpenetrating reinforcement structure.
[0046] The preparation method of the above toughened silk is as follows: First, 10-20μm WC / W2C multiphase particles are prepared by sintering, and then mixed with NiBSi alloy powder (B2-3wt.%, Si <3wt.%, the rest is Ni) by ball milling (speed 100-200rpm) to obtain mixed powder. The mixed powder is filled into a pure nickel tube with an inner diameter of 3-5mm, an outer diameter of 6-8mm, and a length of about 1000mm. After drawing, it becomes a wire with a diameter of about 1.2~2.4mm. In order to ensure the smoothness of the wire drawing process, intermittent wire drawing is adopted, and annealing treatment is performed during this period. The volume fraction of WC / W2C multiphase particles in the toughened wire is 10%-20%.
[0047] The preparation method of the above reinforced wire is as follows: First, WC / W2C multiphase particles of 53-150μm were prepared by casting, and then mixed with NiCrBSi alloy powder (Cr 5-10wt.%, B 2-3wt.%, Si <3wt.%, and the rest is Ni) by ball milling (speed 100-200rpm) to obtain mixed powder. The mixed powder was filled into a pure nickel tube with an inner diameter of 3-5mm, an outer diameter of 6-8mm, and a length of about 1000mm; it was drawn into a wire with a diameter of about 1.2~2.4mm. In order to ensure the smoothness of the wire drawing process, intermittent wire drawing was used, and annealing was performed during this period. The volume fraction of WC / W2C multiphase particles in the strengthening wire is about 30%.
[0048] Secondly, the control of the wire melting transition mode during laser melting is the key link in achieving the preset macro-microstructure of the composite layer. Figure 4 This is a schematic diagram of the reasonable transition mode control of the strengthening yarn and the toughening yarn used in this application. Figure 4As shown, the strengthening / toughening wires are placed facing each other along the laser scanning direction, the negative pole of the power supply is connected to the fixture, and the positive pole is connected to the wire material. By controlling the laser output power and the preheating current of the external power supply, the laser energy and resistance heat can be controlled. Then, under the coordinated control of the two independent heat sources, the strengthening wire can be controlled to melt in the insertion transition mode, while the toughening wire can be controlled to melt in the spreading transition mode. In addition, in order to make the composite layer well formed, the dripping transition mode should be avoided. Finally, a reinforcement structure of uniformly distributed large-scale residual WC / W2C complex phase particles + quasi-continuous network distribution W2C-M6C is formed in the strengthening layer, and a small dense and uniformly distributed native W2C particle reinforcement structure is formed in the toughening layer, as shown in FIG. Figure 4 As shown in Figure 2, the microscopic enhancement phase regulation in the hard / soft heterostructure can achieve further wear resistance and toughness enhancement of thick composite layers or repair layers. The wear mechanism is as follows: Figure 4 shown.
[0049] Next, the solution of the present application will be further described with reference to specific embodiments.
[0050] Example 1 The purpose of Example 1 is to form a two-dimensional layered alternating composite layer single wall specimen on the substrate by alternating cladding, that is, a toughening layer and a strengthening layer appear alternately. For details, see Figure 1 Figure a. Q345 is used as the substrate to be clad, and its size is 50mm×100mm×8mm. The sample thickness is 20mm and the width is 3.2mm.
[0051] The laser light source used in Example 1 of the present application is a fiber laser with a rated power of 2 kW, and the laser spot is circular (the spot size is 5 mm). In the early stage of laser cladding, a preparatory step is first performed, mainly setting the laser output power, preheating current, wire feeding speed, laser scanning speed, shielding gas flow rate and double wire scanning strategy. In this embodiment 1, argon is selected as the side-blowing protective gas, and its flow rate is set to 25L / min and remains unchanged; when the strengthening wire is melted, the laser power is maintained at 1300W, the laser scanning speed is 3mm / s, the wire feeding speed is 5mm / s, and the preheating current is set to 60A. When the toughening wire is melted, the laser power is set to 1000W, and the laser scanning speed is maintained at 3mm / s; the preheating current is set to 70A, and the wire feeding speed is 1mm / s; the diameters of the strengthening wire and the toughening wire are both 1.2mm. Before the laser is emitted, the ends of the strengthening / toughening wires are 1mm away from the surface of the substrate. The two wires are placed opposite to each other, the wire feeding nozzle is placed in a direction parallel to the laser scanning direction, and the angle (acute angle) between the two wires and the horizontal plane is 45°.
[0052] Next, the laser cladding step is performed. First, the toughened wire is melted under the action of synchronous resistance heat and laser energy. The toughened wire melts under the action of an independent heat source and transitions into the molten pool in a spreading transition mode. The molten pool temperature is maintained between 1515K and 1899K. The small-sized WC / W2C multiphase particles in the toughened wire are completely dissolved in the molten pool, releasing W and C elements in the molten pool and inducing the precipitation of W2C particles. The reason is that in the prefabricated mixed powder, after low-energy ball milling, tiny (10~20μm) WC / W2C multiphase particles are uniformly adhered to the larger Ni particles (derived from NiBSi alloy powder). After the Ni particles melt (melting point 1453℃), the high-melting-point WC / W2C carbides can smoothly transition to the molten pool, and then the tiny WC / W2C multiphase particles quickly dissolve and form a radially distributed W (C) element concentration gradient around them, providing the necessary chemical environment for the precipitation of W2C. Therefore, within the appropriate temperature range, the reinforcement phase formed in the toughening layer is a uniformly dense tiny W2C phase, and the size of these native W2C particles is in the range of 1-3 microns; this tiny reinforcement structure not only has no deteriorating effect on the plasticity and toughness of the matrix, but also can maintain a certain wear resistance.
[0053] Compared with the toughened wire, the strengthened wire is in the insertion transition mode under the preset process parameters. Due to the high heat input, the molten pool temperature will reach 1899K or above. In the high heat input wire insertion transition mode, the large-sized WC / W2C multiphase particles (53~150μm) are stably controlled to partially dissolve, and the particles diffuse elements at the solid-liquid interface, which promotes the formation of the M6C phase "buffer layer" around the large-sized residual particles, thereby alleviating the stress concentration phenomenon. The formation of the M6C phase in the Ni-Fe-WC multi-element system is the result of the combined action of a weak carbide-forming element and a strong carbide-forming element. In the temperature range above 1899K, the primary W2C phase will precipitate preferentially. However, W2C is a metastable phase with low stability and easy dissolution in the nickel-based molten pool, and reacts in situ with the Cr-containing liquid phase to form a quasi-continuous network-distributed core-branch W2C-M6C phase composite carbide (10~15μm) in the strengthening layer matrix. The quasi-continuous network distribution of W2C-M6C phase composite carbides not only helps to disperse the stress in the matrix, but also acts as a strong skeletal structure to prevent local wear and failure of the metal matrix, thereby effectively improving the bearing capacity of the composite layer.
[0054] It should be noted that, in this embodiment, the toughening layer is formed first, and then the strengthening layer is formed.
[0055] Figure 5 is a metallographic morphology of the two-dimensional layered alternating structure obtained in Example 1 of the present application. Figure 5 It can be found that there are no defects such as cracks and pores on its surface.
[0056] Example 2 Example 2 is basically the same as Example 1, except that the purpose of Example 2 is to form a three-dimensional layered alternating structure on the substrate by alternating cladding, that is, 3 strengthening layers and 2 toughening layers are alternately stacked along a first direction on a single layer plane, and 2 strengthening layers and 3 toughening layers are alternately stacked along a second direction on adjacent single layer planes in the thickness direction, and the first direction is perpendicular to the second direction, and this is repeated to form a three-dimensional layered alternating structure. For details, see Figure 1 Figure b.
[0057] Performance Testing 1. Wear test The samples were made of Q345 substrate without any cladding, the two-dimensional layered alternating structure prepared in Example 1, and the three-dimensional layered alternating structure obtained in Example 2, and the wear test was carried out. The sample size was 25mm×7mm×7mm, and the test parameters were: the test temperature was room temperature, the grinding wheel size was φ50mm×10mm, the applied load was 49N, the grinding time was 60min, and the speed was 200r / min.
[0058] Figure 6 The wear performance results of the two-dimensional layered alternating structure obtained in Example 1 of the present application, the three-dimensional layered alternating structure obtained in Example 2, and the substrate Q345. Figure 6 , under the same wear test parameters, the wear volume of the substrate is 6.20mm 3 , while the wear volume of the two-dimensional alternating layer is 0.21 mm 3 The wear volume of the three-dimensional alternating composite layer is 0.13 mm 3 , indicating that the wear resistance of the thick and defect-free nickel-based composite layer proposed in this application is nearly 30-48 times higher than that of the substrate.
[0059] 2. Microhardness test The hardness of the sample of Example 1 was measured using a microhardness tester, and the microhardness values of the substrate, toughened zone and strengthened zone were detected along the depth direction. Figure 7 is the hardness test result of the two-dimensional layered alternating structure obtained in Example 1 of the present application. Figure 7 The matrix hardness in the toughened layer is 401HV 0.2 , the matrix hardness in the hardened layer is 680HV 0.2 , base material (Q345) hardness is 187HV 0.2. It can be found that the hardened layer has dense quasi-continuous network distribution of W2C-M6C complex phase carbides, so its hardness can be significantly improved, which is beneficial to improve its wear resistance; while the toughened layer has a relatively small native W2C in the layer, so the hardness improvement is not significant compared with the substrate, but it can effectively maintain the plasticity / toughness of the Ni matrix. Under the close combination and joint action of the hardening / toughening layer, the thick nickel-based composite layer can not only maintain good plasticity and toughness, but also effectively exert its own impact wear resistance.
[0060] To sum up, the core of this application is mainly to meet the higher requirements for surface repair and remanufacturing technology and performance improvement of key metal parts in modern and future high-end manufacturing equipment. In view of the process limitations such as low material utilization and insufficient impact and wear resistance in laser powder cladding of thick particle-reinforced metal-based composite layers under extreme working conditions, based on the idea of integrated laser additive remanufacturing of materials, processes, structures and performance, a heterogeneous twin-wire laser melting technology is proposed, which realizes the controllable preparation of thick layered alternating nickel-based composite layers, significantly improves the impact and wear resistance of thick nickel-based coatings on the surface of metal substrates under extreme working conditions, and provides a green and efficient laser remanufacturing technology for surface repair and strengthening of key components of high-end equipment.
[0061] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.
Claims
1. A method for preparing a thick, impact-resistant and wear-resistant nickel-based composite layer based on heterogeneous twin wires, characterized in that: The method comprises a laser cladding step, wherein the laser cladding step uses toughened wire and reinforced wire as cladding materials, and adopts an alternating cladding method to form a composite layer of alternating toughened layers and reinforced layers on the surface of a substrate.
2. The method for preparing a thick, impact-resistant and wear-resistant nickel-based composite layer based on heterogeneous twin wires according to claim 1, characterized in that: The composite layer is a two-dimensional layered alternating structure or a three-dimensional layered alternating structure.
3. The method for preparing a thick, impact-resistant and wear-resistant nickel-based composite layer based on heterogeneous twin wires according to claim 1, characterized in that: The toughened wire and the reinforced wire are both powder core wires consisting of an outer layer and a filler; The outer layer of the toughened wire is a nickel matrix, and the filler includes NiBSi alloy powder and small-sized WC / W2C multiphase particles; The outer layer of the reinforcing wire is a nickel matrix, and the filler includes NiCrBSi alloy powder and large-sized WC / W2C multiphase particles; The particle size of the small-sized WC / W2C composite phase particles is 10-20 μm, and the particle size of the large-sized WC / W2C composite phase particles is 53-150 μm.
4. The method for preparing a thick, impact-resistant and wear-resistant nickel-based composite layer based on heterogeneous twin wires according to claim 3, characterized in that: The mass fraction of Cr element in the NiCrBSi alloy powder is 5%-10%.
5. The method for preparing a thick, impact-resistant and wear-resistant nickel-based composite layer based on heterogeneous twin wires according to claim 3, characterized in that: The toughened wire and the reinforced wire are respectively made of pure nickel tubes pre-filled with respective fillers through a drawing process, and the diameters of the toughened wire and the reinforced wire are respectively 1.2-2.4 mm.
6. The method for preparing a thick, impact-resistant and wear-resistant nickel-based composite layer based on heterogeneous twin wires according to claim 1, characterized in that: The toughened wire and the reinforcing wire are preheated respectively by independent power supplies, and under the control of the independent power supplies and laser energy, in the laser cladding step, the toughened wire is in a spreading transition mode, and the reinforcing wire is in an insertion transition mode.
7. The method for preparing a thick, impact-resistant and wear-resistant nickel-based composite layer based on heterogeneous twin wires according to claim 6, characterized in that: When laser cladding toughened wire, the laser power is 1000W, the preheating current is 70A, the wire feeding speed is 1mm / s, and the laser scanning speed is 3mm / s; When laser cladding the strengthening wire, the laser power is 1300W, the preheating current is 60A, the wire feeding speed is 5mm / s, and the laser scanning speed is 3mm / s.
8. The method for preparing a thick, impact-resistant and wear-resistant nickel-based composite layer based on heterogeneous twin wires according to claim 7, characterized in that: When laser cladding toughened wire, the temperature of the molten pool formed on the surface of the substrate is 1515K-1899K. When laser cladding strengthened wire, the temperature of the molten pool formed on the surface of the substrate is above 1899K.
9. The method for preparing a thick, impact-resistant and wear-resistant nickel-based composite layer based on heterogeneous twin wires according to claim 1, characterized in that: The substrate includes any one of medium / high entropy alloys, carbon steel, stainless steel, nickel-based alloys, titanium alloys or aluminum alloys.
10. The thick, impact-resistant and wear-resistant nickel-based composite layer prepared by the preparation method according to any one of claims 1 to 9, characterized in that: The thickness of the composite layer is 3-100 mm.